The spectacle and the placeholder: Digital futures for reflective practices in higher education - Ross, Jen (Proceedings of the International Conference on Networked Learning, 2012)
Discourses of reflective writing practices in higher education often demand an orientation towards writing which is highly individual and self-motivated, and which does not acknowledge the socially situated nature of reflective practice. At the same time, the reality of most reflective writing in an educational context, especially when it is produced for assessment purposes, is one of obligation, tacit and explicit criteria, and an audience in the form of a teacher or assessor which must be catered to. The tensions inherent in compulsory reflection have been addressed by some of the literature on reflection, but many authors and teachers have attempted to keep such tensions at bay by ignoring or denying the addressivity and performativity of these practices. This leaves students in a difficult position, where they must be seen to reflect in a way that meets the criteria without appearing to be strategic, knowing or audience-focused. Online reflection can be used to rethink the humanist underpinnings of reflection, allowing teachers and students to question concepts such as ‘authenticity’, ‘consistency’ and ‘development’. By acknowledging the challenges and possibilities of digitality in a high-stakes reflective practice context, we can open these practices up to generative critique and creative reworking, and develop a pedagogy of risky, creative, fragmented digital reflection. Two concepts underpin the proposed pedagogy for online reflection set out in this paper: the spectacle, and the placeholder. The spectacle acknowledges performance, audience, and surveillance, and suggests a playful and knowing orientation towards seeing and being seen. The placeholder gestures towards speed and partiality, and offers fragmentation, appropriation and creativity in the form of the remix. These concepts offer teachers and researchers an alternative vision for reflection that makes the best of what digital environments have to offer, and claims addressivity and performance as useful aspects of learning and teaching in a reflective mode.